PERAN CLINICAL PATHWAY DALAM PERAWATAN STROKE - Paryono; Anindhita, Edina Ufairah; Ar Rochmah, Mawaddah (PERDOSNI, 2025)
Stroke remains a leading cause of disability and mortality worldwide, demanding a comprehensive, structured, and evidence-based approach across the full continuum of care. Clinical pathways (CPs) are integrated, multidisciplinary protocols that operationalize guidelines into day-to-day practice—linking prehospital prenotification, emergency triage, acute treatment, early rehabilitation, and discharge planning. This narrative review synthesizes the rationale, design steps, core components, and clinical evidence for CP implementation in stroke care. Key pathway elements include time-critical targets (e.g., rapid brain imaging for reperfusion candidates), standardized assessments (e.g., National Institutes of Health Stroke Scale / NIHSS), complication prevention bundles (dysphagia screening, venous thromboembolism prophylaxis, glucose and temperature control), mobilization and nutrition plans, patient–caregiver education, and follow-up coordination, all embedded within audit/variance tracking for continuous quality improvement. Evidence indicates that CPs can reduce in-hospital complications, shorten length of stay, lower costs, increase documentation completeness, strengthen adherence to guidelines, and enhance patient satisfaction and team collaboration. Effects on hard clinical outcomes (mortality, long-term disability) are more variable and appear contingent on stroke-unit infrastructure, resource readiness, team training, and local adaptation. Overall, CPs remain a strategic tool within organized stroke systems, translating evidence into timely, coordinated care and supporting iterative improvements in quality and efficiency. Keywords: Clinical pathway, stroke, evidence-based medicine, multidisciplinary care, patient outcomes